A journey in bioinspired supramolecular chemistry: from molecular tweezers to small molecules that target myotonic dystrophy - Zimmerman, Steven C. (Beilstein Journal of Organic Chemistry, 2016)
This review summarizes part of the author’s research in the area of supramolecular chemistry, beginning with his early life influences and early career efforts in molecular recognition, especially molecular tweezers. Although designed to complex DNA, these hosts proved more applicable to the field of host–guest chemistry. This early experience and interest in intercalation ultimately led to the current efforts to develop small molecule therapeutic agents for myotonic dystrophy using a rational design approach that heavily relies on principles of supramolecular chemistry. How this work was influenced by that of others in the field and the evolution of each area of research is highlighted with selected examples.
Keywords: catenanes; intercalation; macrocycles; multi-target drug discovery; RNA recognition; RNase mimic